30‐Day morbidity and mortality of bariatric metabolic surgery in adolescence during the COVID‐19 pandemic – The GENEVA study. Issue 12 (8th July 2021) - Singhal, Rishi; Wiggins, Tom; Super, Jonathan; Alqahtani, Aayed; Nadler, Evan P.; Ludwig, Christian; Tahrani, Abd; Mahawar, Kamal; ,
Summary: Background: Metabolic and bariatric surgery (MBS) is an effective treatment for adolescents with severe obesity. Objectives: This study examined the safety of MBS in adolescents during the coronavirus disease 2019 (COVID‐19) pandemic. Methods: This was a global, multicentre and observational cohort study of MBS performed between May 01, 2020, and October 10, 2020, in 68 centres from 24 countries. Data collection included in‐hospital and 30‐day COVID‐19 and surgery‐specific morbidity/mortality. Results: One hundred and seventy adolescent patients (mean age: 17.75 ± 1.30 years), mostly females (n = 122, 71.8%), underwent MBS during the study period. The mean pre‐operative weight and body mass index were 122.16 ± 15.92 kg and 43.7 ± 7.11 kg/m 2, respectively. Although majority of patients had pre‐operative testing for severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) (n = 146; 85.9%), only 42.4% (n = 72) of the patients were asked to self‐isolate pre‐operatively. Two patients developed symptomatic SARS‐CoV‐2 infection post‐operatively (1.2%). The overall complication rate was 5.3% (n = 9). There was no mortality in this cohort. Conclusions: MBS in adolescents with obesity is safe during the COVID‐19 pandemic when performed within the context of local precautionary procedures (such as pre‐operative testing). The 30‐day morbidity rates were similar to those reported pre‐pandemic. These data will help facilitate the safe re‐introduction of MBS services for this group of patients.